Governing agricultural migrant workers as an "emergency": converging approaches in Northern and Southern Italian rural towns. (8th September 2017) - Semprebon, Michela; Marzorati, Roberta; Garrapa, Anna Mary
Abstract: Rosarno and Sermide are two small towns in Southern and Northern Italy, which are both part of a manual‐labour circuit of agricultural work. The article presents an analysis of governance structures in these towns and, by bringing together the literature on migrants' agricultural labour and local policy‐making, explores how public actors address migrant seasonal agricultural workers' needs to investigate outcomes of inclusion and exclusion. The article builds on qualitative research, conducted between 2012 and 2015, to propose a North‐South intra‐country comparison of local policy‐making. The findings show the emergency nature of local administrations' approaches and the critical role of civil society. They highlight the extent to which responses diverge or converge in means and scale, while stressing their convergence in scope to limit migrants' visibility.